Experimental study тензорных models of the presentation symbol - Винник, Д. Н. (Problems of Informatization and Control, 2007)
On base of designed software to explored particularities of the presentation symbol (литер) tensor miscellaneous rank - from 4-go (9x9) before 8-go (729x729). For all greater letters determined all possible numerical features of the tensor (the invariants of the number, factors of the multinomial of the indicative equation, own chisla.), which are brought about pixel. They Are Received statistical data, on the grounds of which, elected best of the number, factors of the multinomial of the indicative equation. Organized analysis result for tensor of the miscellaneous rank